Transcriptomics reveals age-related changes in ion transport–related factors in yak lungs - Xie, Xiating; Wei, Yating; Cui, Yan; Zhang, Qian; Lu, Hongqin; Chen, Liang; He, Junfeng (Frontiers in Veterinary Science, 2024)
Yaks inhabit high-altitude,low-oxygen regions,where ion transport functions play a crucial role in maintaining intracellular and extracellular ionic balance and regulating pulmonary vascular tension.These functions affect pulmonary ventilation and blood flow rate, aiding tissue development and enhancing oxygen transfer efficiency, thus facilitating better adaptation to hypoxic environments. To investigate the regulatory mechanisms of ion transport-related factors on the growth and development of yak lungs,we employed RNA sequencing (RNA-seq)for sequencing the transcriptome in the lung tissues of neonatal (1-day-old), juvenile (1-year-old), and adult (4-year-old) yaks. We also performed differential gene expression and functional analyses. The results yielded 26 genes associated with ion transport, mainly enriched in the salivary and pancreatic secretion pathways. Finally, we used several methods including quantitative polymerase chain reaction (qRT-PCR), and Western blotting(WB), immunohistochemical(IHC) and immunofluorescence(IF) staining to determine the distribution of the expression of the ion transport genes FOXI1, KCNMA1, and SLC12A2 in yak lung tissues. qRT-PCR and WB results indicated that mRNA and protein relative expression levels of FOXI1 and SLC12A2 were significantly higher in neonatal yaks than in juvenile and adult yaks (all P < 0.05), whereas those of KCNMA1 were significantly higher in adult yaks than in neonatal and juvenile yaks (all P < 0.05). IHC and IF results demonstrated that FOXI1, KCNMA1, and SLC12A2 were distributed among the epithelial mucosal layers (including ciliated, goblet, and Clara cells) of the yaks' bronchi and their branches in the lungs across different age groups of yak.Therefore, our results suggested that FOXI1, KCNMA1, and SLC12A2 may be strongly associated with the development and aging processes in yak lungs. These results provide insights into the molecular mechanisms underlying the yak's adaptation to high-altitude environments and valuable references for further research.